A1 8 Armageddon: The Christmas Special! - Holmes, Pippa; Bujdoso, Kieran; Stentiford, Madeleine; Tasyaka, Andrea (Physics Special Topics, 2024)
Santa (Bruce Willis) has lost control of his reindeer, they’re going to crash! Using the information gathered over the last four papers about Armageddon (1998), we investigate the physical consequences of the impact. Approximating Santa and his sleigh as an asteroid, we found that the transient crater diameter would be 32.18 km, with a final size of 50.83 km. Additionally, with the knowledge of the crater being complex, we found the central peak (hereafter named ‘Santa Mountain’) to have a height of 2.73 km. In another scenario, we calculated the velocity that Santa would have to travel at to knock the asteroid off of a collision course in a similar manner to the DART mission, and find it would take a speed of 4.42 × 10^11 m/s to save Christmas.